Synthesis of Bentonite-TiO2 Bionanocomposite for Photodegradation of Used Lubricating Oil - Sri Hilma Siregar; Hasmalina Nasution; Rennadya Sekar Fitri; Aulia Rizki Ramadhanti (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
Used lubricating oil waste contains heavy metal components which, if they enter the water, will block light. Used lubricants include toxic and hazardous waste (B3) so they need further processing before being reused or thrown away, because they are dangerous for human health and the environment. This research aims to determine the ability or effectiveness of the Bentonite-TiO2 composite in degrading used lubricating oil. The research began by synthesizing Bentonite-TiO2 where the composite results obtained were characterized. Based on the results of the FTIR spectrum analysis of Bentonite-TiO2, Ti was successfully modified in bentonite because the wave number 1419.84 cm-1 shows the presence of Al-O groups and the wave number 1423.92 cm-1 shows the presence of Ti-O-Ti vibrations. The results of XRD characterization show that TiO2 has formed in the bentonite-TiO2 composite, this makes the bentonite-TiO2 more stable and can be used as photocatalysis in the processing of used lubricating oil. The results of SEM-EDX analysis of Bentonite-TiO2 show the chemical composition of C, O, Al, Si, Ca, and Ti. In photodegradation, the mass variation viscosity value with an optimum time of 5 hours is the highest viscosity value, namely with a viscosity value of 5.11 cSt.